Coccoloba floresii (Polygonaceae), a new species from Chiapas (Mexico) - Arnelas Seco, I. (2015)
Coccoloba floresii is here described as a new species from Mexico. Morphological characters of the leaf, inflorescence, and fruit show discontinuities among populations of C. floresii and its relatives, C. barbadensis and C. cozumelensis. In addition, C. floresii is exclusive of the tropical dry forests of Central Depression and Plateau of Chiapas (Mexico) at high elevations. © 2015 Magnolia Press.